2020
DOI: 10.1101/2020.08.27.271080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age and gender dependence of liver diffusion parameters and the evidence of intravoxel incoherent motion modelling of perfusion component is constrained by diffusion component

Abstract: ObjectivesTo establish reference values for middle aged subjects and investigate age and gender dependence of liver diffusion MRI parameters.MethodsThe IVIM type of liver diffusion scan was based on a single-shot spin-echo type echo-planar sequence using a 1.5-T magnet with 16 b-values. DDVD (diffusion-derived vessel density) was the signal difference between b=0 and b=2 s/mm2 images after removing visible vessels. IVIM analysis was performed with full-fitting and segmented-fitting, and with threshold b-value … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…However, the observed PF and D fast results gave contradictory results compared with DDVD and known vessel physiology of the liver aging, with both PF and D fast measures showed age-dependent elevation. This was observed when we used segmentation fitting or full fitting, and observed when we performed bi-exponential decay fitting included or excluded b=0 data (3). We concluded that the quantification of both PF and D fast is constrained by D slow , i.e., lower D slow leads to higher PF and D fast measurements, even PF and D fast did not increase or even declined.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…However, the observed PF and D fast results gave contradictory results compared with DDVD and known vessel physiology of the liver aging, with both PF and D fast measures showed age-dependent elevation. This was observed when we used segmentation fitting or full fitting, and observed when we performed bi-exponential decay fitting included or excluded b=0 data (3). We concluded that the quantification of both PF and D fast is constrained by D slow , i.e., lower D slow leads to higher PF and D fast measurements, even PF and D fast did not increase or even declined.…”
supporting
confidence: 54%
“…Recently we reported that, for the liver, IVIM modeling of the perfusion component is constrained by the diffusion component, and a reduced D slow measure leads to artificially higher PF and D fast measures (3). In this study of 26 male volunteers (age: 22-69 years) and 36 female volunteers (age: 20-71 years), we demonstrated an age-dependent liver D slow decline, which is expected to be caused by an agedependent iron deposition increase, an age-dependent fat deposition increase, and also a reduction of vasculature in the healthy aging livers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in NMR in Biomedicine we recently published that, at least for the liver, IVIM modeling of the perfusion component is constrained by the diffusion component, and a reduced D slow measure leads to artificially higher PF and D fast measures. 1 Our results may have important implications for interpreting previously published literature on IVIM and for designing future IVIM studies. For one example, many previous works have reported that liver steatosis is associated with an increased PF.…”
Section: Observed Paradoxical Perfusion Fraction Elevation In Steatotmentioning
confidence: 69%
“…In a study evaluating IVIM measure of liver fibrosis, we reported a Pearson correlation coefficient r of 0.865 between PF and D fast . 19 Although it is more difficult to measure D fast precisely, 18,20 the point mentioned above is also likely to have implications for interpreting D fast results, as a reduced D slow measure can lead to an artificially higher D fast measure as well 1 .…”
Section: Observed Paradoxical Perfusion Fraction Elevation In Steatotmentioning
confidence: 99%